Improving The Methodology For The Development Of Mediacompetency Of Students Of Higher Educational Institutions (On The Example Of The Educational Science” Informatics And Digital Technologies") - Qudratov Akbar Nurullo o‘g‘li (Academia One Publishing, 2024)
this article highlights the improvement of the methodology for the development of mediacompetency of students of higher education institutions.
Keywords: Mediamadaniyat; digital education; Media Technology